Supercapacitor energy storage systems for lighting systems with combined power supply - Demyd Pekur; Yuriy Kolomzarov; Vitaliy Kostylyov; Viktor Sorokin; Vasyl Kornaga; Roman Korkishko; Yurii Nikolaenko (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Modern continuous lighting systems use powerful high-performance LEDs as light sources and an important task is to begin using alternative renewable energy sources for their power supply (including during the day). The simplest of the renewable energy sources is photovoltaic solar energy converter. However, solar photovoltaic generation depends significantly on many factors — geographical location, time of day, state of the atmosphere, time of year and the like. In addition, photovoltaic generation depends on the weather conditions and cloudiness, which makes it unstable and prone to change drastically (by an order of magnitude) during daylight hours. Therefore, an important element of the power system based on renewable energy sources is the system of accumulation of generated energy. The method of power stabilization using supercapacitors for systems with a significant change in power generation in the electrical power system is analyzed. The paper offers design principles of the power supply systems for powerful LEDs with supercapacitor energy storage devices intended to make the use of energy from sources with variable generation more efficient. The systems with supercapacitor-based drives, which allow to ensure stable operation of the lighting system when the power supply from an alternative source is absent or reduced, provide high safety and reliability, and have a significantly longer service life than battery-based energy storage systems.